Obesity in Children - Mulyadi Mulyadi; Soepardi Soedibyo (Paediatrica Indonesiana, 1997)
Obesity in Indonesia starts to become a problem, considering the tenÂdency for the prevalence rate to get higher. Data on obesity in Indonesian children are very limited and criteria for nutritional status and obesity in children are yet to be deÂfined. Although, unlike in adults, side effects of obesity in children rarely become a health problem, obesity in children has a tendency to develop into adult obesity which is difficult to manage. That is why early management is very important. Management of obesity in children includes effort to increase understanding of obesity problems, build up a motivation to improve the condition, limitation of energy intake, increasing energy uptake by physical exercise, and management of psychological disorders. For those reasons, a full support from all family members is needed. Growth and developÂment monitoring need to be increased so an optimal growth and development is reached.